Comparison of Phosphohistone H3 Immunohistochemical Staining, Ki-67, and H&E Mitotic Count in Invasive Breast Carcinoma - S. Woo, Jennifer; A. Moatamed, Neda; S. Sullivan, Peggy; Y. Lu, David; Callahan, Rena; Apple, Sophia (Journal of Breast Cancer Survival, 2015)
The mitotic count is the most frequent reason for discordance between pathologists in modified Bloom and Richardson (mBR) scoring. Recently, the phosphohistone H3 (PHH3) immunohistochemical stain has been proposed as a potential surrogate marker for mitotic figures. This study examines the differences between H&E mitotic count, PHH3 mitotic count, and Ki-67 index in invasive breast carcinoma. A retrospective review of invasive breast carcinoma cases from 2013- 2014 was performed. H&E and PHH3 mitotic counts were assigned a mitotic score of 1 to 3 using mBR criteria. Ki-67 index was categorized into a three-grade system: <10% (low), 10 - <20% (intermediate), and >20% (high). A total of 451 cases were evaluated. PHH3 versus H&E mitotic count changed mBR scores in 24% of cases, upgrading in 23% and downgrading in 1%. A total of 431 cases had both Ki-67 and PHH3 available for comparison. Both H&E and PHH3 mitotic scores correlated with Ki-67 in 51% of cases; however, PHH3 had better correlation. We conclude that PHH3 in breast carcinoma allows for a more sensitive and practical approach in the identification of mitotic figures. PHH3 IHC is useful as a confirmatory tool in assessing the final mitotic score for more accurate mBR scoring and grading. In this study, 48 out of 451 (10.6%) of patients had a significant upgrade that may change the patient's treatment plans, including the addition of chemotherapy
Keywords: phosphohistone-H3 (PHH3); mitotic count; Ki-67; invasive breast carcinoma; modified Bloom and Richardson score